Towards the Professionalization of Students Prepared to Become Teachers - Gani, BeatriÃ§e (Richtmann Publishing, 2012)
The study is focused on mentoring of the teaching practice for student teachers. It aims at assessing their formation basedon the application of theoretical knowledge in professional practise, taking into consideration new perspectives about the meaningof teaching effectively. The following study is based on a survey of students conducted by student teachers, based on thecharacteristics of the profession of teachers and valued professional competencies as necessary to achieve. Review and analysis ofdata allows us to appreciate to what extent the previous experiences, relationships with companion pedagogue and teacher mentor, aswell as all the supporting factors in professional practice, condition the effectiveness of the professional practice of the student teacher.Professional practice, viewed as a coordination of theoretical knowledge with practical skills and adaptation to the school context, makesus think about the choice of different strategies in the preparation of teachers skilled in the function of a successful teaching.